The relationship between the fatty acid composition of the diet and that of plasma triacylglycerol, plasma esterified cholesterol and subcutaneous adipose tissue in man - Van Staden, Ernesta (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Nutrition) -- University of Stellenbosch, 1989.